Effects of Afforestation Restoration on Soil Potential N2O Emission and Denitrifying Bacteria After Farmland Abandonment in the Chinese Loess Plateau - Deng, Na; Wang, Honglei; Hu, Shu; Jiao, Juying (Frontiers in Microbiology, 2019)
Denitrification is a critical component of soil nitrogen (N) cycling, including its role in the production and loss of nitrous oxide (N2O) from the soil system. However, restoration effects on the contribution of denitrification to soil N2O emissions, the abundance and diversity of denitrifying bacteria, and relationships among N2O emissions, soil properties, and denitrifying bacterial community composition remains poorly known. This is particularly true for fragile semiarid ecosystems. In order to address this knowledge gap, we utilized 42-year (y) chronosequence of Robinia pseudoacacia plantations in the Chinese hilly-gullied Loess Plateau. Soil potential N2O emission rates were measured using anaerobic incubation experiments. Quantitative polymerase chain reaction and Illumina MiSeq high-throughput sequencing were used to reveal the abundance and community composition of denitrifying bacteria. In this study, the afforestation practices following farmland abandonment had a strong negative effect on soil potential N2O emission rates during the first 33 years. However, potential N2O emission rates steadily increased in 42 years of restoration, leading to enhanced potential risk of greenhouse gas emissions. Furthermore, active afforestation increased the abundance of denitrifying functional genes, and enhanced microbial biomass. Actinobacteria and Proteobacteria were the dominant denitrifying bacterial phyla in the 0 to 33-y old sites, while the 42-y sites were dominated by Planctomycetes and Actinobacteria, implying that the restoration performed at these sites promoted soil microbial succession. Finally, correlation analyses revealed that soil organic carbon concentrations had the strongest relationship with potential N2O emission rates, followed by the abundance of the nosZ functional gene, bulk density, and the abundance of Bradyrhizobium and Variovorax across restoration stages. Taken together, our data suggest above-ground restoration of plant communities results in microbial community succession, improved soil quality, and significantly altered N2O emissions.